Cavity-plasmon waveguides: Multiple scattering calculations of dispersion in weakly coupled dielectric nanocavities in a metallic host material - G. Gantzounis; N. Stefanou (Physical Review B, 2006)
We propose a different type of plasmonic waveguide which consists of identical dielectric nanocavities, periodically arranged along a line, in a metallic material. The dispersion relations for the different guiding modes are obtained by means of exact mutliple scattering calculations and also by a simple tight-binding model which allows a straightforward analysis of the underlying physics. This type of waveguide combines strong lateral localization and no radiative losses with efficient transmission of light through sharp bends. We show how one can overcome absorptive losses by introducing optical gain media into the cavities and, also, how one can design such waveguides for single-mode operation over a given frequency range by using nonspherical cavities.